Delayed Restart of Antithrombotic Therapy and Rates of Adverse Events in Subdural Hematomas. (1st September 2019) - Chaker, Anisse N; Rosenberg, David; Ryoo, James S; Rosinski, Clayton L; Patil, Shashank; Geever, Brett; Patel, Saavan; Chiu, Ryan Guan; Barrington, Nikki; Mudreac, Andrew; Fuentes, Angelica; Zhu, Amy; et al.
Abstract: INTRODUCTION: The management of subdural hematoma (SDH) in the setting of antithrombotic (AT) therapy, which includes antiplatelet and anticoagulant therapy, is especially challenging. While there exists consensus that AT should be discontinued during initial workup and surgical treatment of SDH, guidance regarding whether and when to restart AT is lacking. This study aims to characterize the association between the timing of AT restart and rates of thrombotic and hemorrhagic adverse events among SDH patients previously on AT in order to inform future clinical decision making. METHODS: A 10-yr retrospective analysis of SDH patients treated with antiplatelet or anticoagulant therapy was performed. Patients were grouped based on time to restart of AT therapy from admission (within 14, 15–29, 30–44, 45–59 d, and not within 60 d), and multivariable regression was used to compare the rates of adverse events between these groups. Adverse events included bleeding, thromboembolism, myocardial infarction, deep vein thrombosis, and stroke. RESULTS: A total of 226 consecutive patients were included in this analysis. Groups based on AT restart time were similar in terms of demographics and rates of comorbidities. The rates of coronary artery disease, operative treatment, and chronicity of SDH differed significantly between groups. The 45 to 59 d group had significantly fewer total complications compared to the 60 + day group ( P = .016) and trended towards fewer complications than the within 14 d group and the 15 to 29 d group ( P = .062 and .065, respectively). CONCLUSION: Evidence supports a lower rate of overall adverse events in patients restarted between 45 and 59 d postadmission. This restart window may be the optimal time point for potential future clinical trials.